Suppression of MiR130a-3p Using CRISPR/Cas9 Induces Proliferation and Migration of Non-Small Cell Lung Cancer Cell Line - Nur Ainina Abdollah; Nabil Izzatie Mohamad Safiai; Muhammad Khairi Ahmad; Kumitaa Theva Das; Siti Razila Abdul Razak (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Molecular alterations of microRNA130a (miR130a) are observed in many types of cancers, including non-small cell lung cancer (NSCLC). However, the role of miR130a in NSCLC has been poorly studied.METHODS: In this study, clustered regularly interspaced short palindromic repeat (CRISPR)-Cas9 was utilised to knockdown miR130a. The gRNA was designed to target the stem loop, 3’ and 5’ sites of miR130a and stably expressed in A549 cells. Post-treatment, mature levels of miR130a-3p and 5p were quantified, and proliferation and migration assays were conducted.RESULTS: Result showed significant suppression of miR130a-3p and -5p by two and three-fold respectively, when the CRISPR/Cas9 targeted at the 3’ site and stem loop of the miR130a gene. Suppression of miR130a-3p significantly increased the growth and migration of A549 cells, but no significant changes were observed in cells with suppressed expression of miR130a-5p.CONCLUSION: Our encouraging results highlight that the suppression of the miR130a is achievable using CRISPR/Cas9, and suppression of the miR-130a-3p could play an important role in the regulation of NSCLC.KEYWORDS: miR130a, CRISPR-Cas9, non-small cell lung cancer